Conceptualizing and developing effective practices of service learning in UUM - Yusof, Norhafezah (Universiti Utara Malaysia, 2020)
Service learning is a method of teaching and learning that bridges classroom experiences with community activities. It centres on the improvement of assets of the selected community and co-creating knowledge through planned tasks (Hamerlinck & Plaut, 2014). The main aim is to produce meaningful learning experiences through experiential learning. Service learning is one of the pedagogical strategies that could enhance teaching and learning skills in the 21st century via its meaningful and innovative learning outcomes. It has been identified as one of the ten high impact practices for engaging learners (AAC&U & NLC, 2007). In line with the recent development on high impact practices that are seen globally, Malaysia has been enhancing its teaching quality via the Ministry of Education (MoE) by introducing high impact practices that include service learning or better known as SULAM.